Stone tool backing and adhesion in hunting weaponry: First results of an experimental program. (October 2022) - Pargeter, Justin; Chen, Caleb; Buchanan, Briggs; Fisch, Michael; Bebber, Michelle; Eren, Metin I.
Highlights: Stone tool backing has been proposed to increase lithic adhesion to wooden shafts. We conducted a ballistics experiment between backed and non-backed stone tools. Backed stone tools were less likely to stick to wooden shafts than were non-backed tools. More experiments are needed. Abstract: Stone tool backing repeatedly occurred on several continents throughout the Pleistocene and Holocene. Yet, any potential utilitarian advantages or disadvantages of backed stone tools relative to non-backed tools has been experimentally under-explored. Modern engineering experiments involving adhesion mechanics suggest an inverse relationship between surface area and the strength of a bond, especially on heterogeneous surfaces like stone. Some stone flakes, especially those with longer edges, may have been backed to make them easier to hold and safer to use. Further, Stone Age humans hafted both backed and un-backed tools for millennia in many parts of the world, suggesting effective hafting could occur with or without backing. Backing itself is a relatively simple technique providing toolmakers with an easy way to shape stone flakes. Some archaeologists have even hypothesized backed tool shaping was an end to communicate social information via stone symbols. This is the first pilot in a series of experiments testing a straightforward null and alternative hypothesis assessing the relationship between backing and adhesion and shaft damage with respect to projectile weaponry. Overall, our experimental results suggested two central conclusions with respect to backing. First, backing does not appear to improve adhesion but instead significantly worsens it. Second, laterally backed tools seem to increase the chances of shaft splitting relative to laterally hafted non-backed tools. Assuming for a moment that our results are supported by our future experimental research, our findings suggest that factors other than increased adhesion, such as intentional 'failure, ' drift, or non-functional bias during social signaling or symbolic communication events, may have been responsible for the adoption and transmission of backed tools.